Pengaruh Current Ratio, Return on Equity, Debt to Equity Ratio dan Earning per Share Terhadap Dividend Payout Ratio Pada PT ACE Hardware Indonesia Tbk - Agustin, Lena (Program Studi Sistem Informasi Akuntansi Kampus Kota Sukabumi, 2024)
Dividend policy is related to determining how much profit will be distributed to shareholders, and determining how much should be reinvested as retained earnings. This research aims to empirically test the factors that are considered to influence dividend policy. The independent variables in this research include the Current Ratio, Capital Profitability, Solvency Ratio and Market Ratio. Meanwhile, the dependent variable is the Dividend Payout Ratio. This type of research is quantitative research, and uses secondary data. The sampling method used was a time series, obtained from PT ACE Hardware Indonesia Tbk which distributed dividends consecutively during the research period, namely 2012-2022. The data analysis technique used is multiple linear regression analysis. The research results show that the ROE and EPS variables have a contribution to the DPR, while CR and DER have no contribution to the DPR.